Policing the womb: invisible women and the criminalization of motherhood - Goodwin, Michele (Cambridge University Press, 2020)
"This is not a work of fiction, although I wish it were. Some of the cases described here could evoke the imagery evoked by Mary Shelly, author of Frankenstein, or, The Modern Prometheus, who tells a horror story about a young, rogue scientist who creates an unsightly monster through clandestine, aberrant experimentation. Although Frankenstein is the name of the monster's creator, Dr. Victor Frankenstein, readers would be forgiven for debating who the real monster happens to be. In Policing the Womb, the story of Marlise Muñoz comes to mind. Brain dead, decomposing in a Texas hospital, under legislation from the state, forced to gestate a barely developing fetus while her body decays and the anomalies in the fetus mount. Eventually, it will be reported that the fetus is hydrocephalic, which means severe brain damage in this case and water or fluid developing on its brain. Medical reports will also show that the fetus is not developing its lower extremities. The state knows brain death is irreversible"--